A review of upgradation of energy-efficient sustainable commercial greenhouses in Middle East climatic conditions - Subin Mattara Chalill (De Gruyter, 2021)
Greenhouse farming is considered as one of the most scientific approaches in agriculture, which are suitable for all climatic conditions, especially in Middle East, North America, and Europe. Sustainable greenhouses are innovative farming facilities for healthy vegetables and fruits in a controlled, conditioned indoor space. This article presents a literature review on the upgradation of a conventional to a sustainable greenhouse using modern engineering concept. This includes maintaining fully controlled indoor conditions such as temperature, relative humidity, and air velocity for specific agronomical parameters. The influence and improvements in upgradation of various heating, ventilation, and air-conditioning (HVAC) with the associated control systems and covering materials to reduce the energy consumption have been reviewed. Financial viability of conventional as well as upgraded greenhouses is highlighted. In Middle East climatic conditions, the major challenge is to control the optimal range of temperature (18–21°C), relative humidity (55 to 75%), and air velocity (0–1.3 m/s). It is found that the upgraded HVAC systems with climate control modules can increase the crop yield by 30%. Scientifically selected polycarbonate sheet covering materials are also found to increase the crop yield by up to 15% more than the conventional commercial greenhouses.